(untitled) (Revista LIDER, 2020)
This paper analyzes the importance of local players participation in the implementation of local policies for local economic development processes; for which, a case study is applied to El Alto city, Bolivia; considering as a starting point, the endogenous development theory, which explains the development, growth and structural change processes within an area, based on a territorial perspective, not only involving the efficient use of resources and development potentiality, but also the creation and dissemination of productive systems innovations, flexible production organization, generation of agglomeration economies, institutional development, and Municipal Government actions regarding policy development; the latter measured or evaluated through efficiency criterion. In this regard, the development process of El Alto city from 1985 - 2008 made this city become the third most important city of Bolivia.